Herpes simplex esophagitis a cause of odynophagia in young patient: case report - Nikolova, Dafina; Volkanovska, Anche; Andreevski, Vladimir; Isahi, Urim (My University, 2020)
Objectives: Herpes simplex esophagitis is usually found in immunosuppresed patient, those with malignancy, patient with AIDS, patient treated with immunosupresive therapy and in terminally ill patients. Very rarely it can be found in healthy, immunocompetent individuals. We present a case of a young patient with herpes simplex esophagitis manifested with odynophagia, retrosternal pain and fever. Case presentation: 18 years old patient referred to our clinic because of acute and severe odynophagia, retrosternal pain and fever in the last five days. She had no previous medical conditions. On physical examination the patient had fever up to 39C and tachycardia of 105/min. She had no abdominal tenderness, no palpable masses or hepatosplenomegaly. Laboratory analysis showed normal total white blood cell (WBC) count of 4.7x109/L. The patient underwent an upper gastrointestinal endoscopy. Upper gastrointestinal endoscopy revealed friable and inflamated esophageal epithelium with multiple conflu- ent ulcerations. Several biopsies were taken and patohystological analysis showed inflamamatory infiltrate with acute vas- cular proliferation and presence of lymphoid accumulations and eosinophils. This finding showed acute erosive esophagi- tis. In addition, HSV serology was done and HSV IgM and HSV IgG were positive. Blood serology for CMV IgM was negative. The patient was treated with oral acyclovir 200mg five times a day, for two weeks. Improvement of the symptoms was reported the second day, with complete resolution after completing the 14 days course of antiviral treatment. Conclusion: Herpes simplex esophagitis is a condition associated with immunosuppresd patient. It is typically presented with odynophagia, severe retrosternal pain and fever. Rarely, it can be found in immunocompetant patient and effectively treated with antiviral medications.
Keywords: odynophagia; herpes simplex virus; esophagitis